Panhellenic Congress News: innovation in the academic world - He, Melanie C. (Journal of Thoracic Disease; Vol 6, No 12 (December 31, 2014): Journal of Thoracic Disease, 2014)
On November 20, everything on the congress site was well-organized. Under the tranquil, comfortable and pleasant atmosphere, the Panhellenic Congress on respiratory and occupational chest diseases: consensus and controversy was officially held in Thessaloniki, Greece from November 20th to 23rd, 2014. This is one of the most important congresses in northern Greece in the field of thoracic disease held by every two years since 1984.